INTEGRATION OF TOPOGRAPHIC DATA INTO 3D CIVIL SOFTWARE AS ROAD DESIGN SUPPORT - Ali, Akbar; Mustakim, Mustakim; Jabir, Muh. (International Journal of Civil Engineering and Infrastructure, 2025)
Accurate topographic mapping is a critical component in strategic planning and architectural design of road infrastructure, particularly in the assessment of optimal routing, evaluation of slope stability, and quantification of excavation volumes and landfill requirements. Advances in mapping technologies, such as geographic information systems (GIS), have significantly improved the resolution and precision of topographic data when compared to traditional methodologies. Utilizing Civil 3D software facilitates a faster and more effective approach to contour data analysis and visualization, enabling superior planning and informed decisionmaking. In addition, Civil 3D offers a number of functions, including assessment, volume cut and fill calculations, and drainage analysis, which have proven invaluable in the design of roads and related infrastructure. The researchers employed a feasibility methodology in their study, using Google Earth software as a tool to acquire satellite imagery, while Global Mapper was used for the extraction of coordinate data from each designated point; the processing of the resulting coordinates was performed in Autodesk Civil 3D for the design of a road spanning a total length of 970.70 kilometers. The purpose of this study was to formulate a more systematic and efficient methodology for the integration of topographic data to improve the accuracy and efficacy of 3D model-based road design. The proposed methodology includes analysis of state-of-the-art topographic mapping techniques, evaluation of data compatibility with 3D civil engineering software, and development of strategies for optimization of data formats and processing. keywords : Topography, Civil 3D, Road Planning, Contour Visualization, Gowa Regency